The Effect of Numbered Head Learning Method Together (NHT) on Student Learning Outcomes in The Subject of Creed and Malak in Class XI MA Aisyiyah Binjai - Khairudin, Ahmad (Lembaga Riset Mutiara Akbar, 2024)
This study aims to find out: 1) the Numbered Head Together (NHT) learning method, 2) student learning outcomes, 3) the significant influence of the Head Together (NHT) method on student learning outcomes. The problem in this study is the lack of variety of learning methods that make student learning outcomes low. This research uses quantitative methods with a descriptive approach. The population in this study is the entire class XI MA Aisyiyah Binjai. The sampling with nonprobability sampling and obtained a sample of 46 people. Data collection techniques using questionnaires. Data analysis techniques with correlation test and T test. Based on the results of the study, it is known that the Numbered Head Together (NHT) learning method affects student learning outcomes. This can be proven through correlation by using the product moment correlation formula obtained at 0.5 with a high correlation level. The results of the t test calculation in this study obtained a Tcount of 3.14 with a significance level of 5% obtained Ttable of 2.015. It can be seen the value of Tcalculate > Ttable then Ho rejected and Ha accepted. In other words, it can be concluded that there is a significant influence between the Numbered Head Together (NHT) learning method on student learning outcomes.